Pengaruh Pendidikan Agama Islam Dalam Keluarga Terhadap Pembentukan Akhlak Remaja di Desa Jemundo Kecamatan Taman Kabupaten Sidoarjo - Ach. Nur Aulia Akbar; Musawir Musawir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
One of the Islamic religious education provided by parents to adolescents is Islamic religious education by example, habituation, attention, advice and punishment because through this method children will gain experience and habits from parents in everyday life. However, modernization today has eroded the morals of today's adolescents so that the role of the family is needed wisely in the cultivation of religion from an early age. The purpose of this study is to (1) explain the application of Islamic Education in the family to the formation of adolescent morals in Jemundo Village, Taman District, Sidoarjo Regency. (2) explain the morals of the majority in Jemundo Village, Taman District, Sidoarjo Regency. (3) explain how much influence Islamic religious education has in Jemundo Village, Taman District, Sidoarjo Regency. This research method is quantitative with two populations, namely the informant population and the respondent population and the number of samples as many as 11 informant samples and 32 respondent samples. Data collection techniques in this study are questionnaires, interviews and documentation with data analysis techniques in the form of percentage analysis and product moment This research obtained several results, namely (1) Islamic Religious Education in families in Jemundo Village, can be applied well. This is evidenced by the percentage obtained 74.2%, which shows that Islamic Education in the family is classified as good between 68.01% - 84.01%. (2) The formation of youth morals in Jemundo Village can be categorized as good. This is based on the calculation of the percentage obtained a value of 82.1% classified as very good, which shows that the formation of adolescents is classified as very good, because it is between 84.01 – 100%. (3) Based on the results of the correlation test analysis, rxy calculate for N = 30 obtained a value of 0.564. If consulted in the table